Risk factors of preterm birth and low birth weight neonates among Roma and non-Roma mothers - Diabelková, Jana; Rimárová, Kvetoslava; Urdzík, Peter; Dorko, Erik; Bušová, Andrea (Central European Journal of Public Health, 2018)
OBJECTIVE: This study analyses the differences in birth outcomes between Roma and non-Roma mothers and investigates the potential causes of such differences. METHODS: We conducted a retrospective cohort study of 1,989 non-Roma and 799 Roma mothers who gave birth in 2014 and 2015 at the Gynaecology and Obstetrics Clinic of Louis Pasteur University Hospital in Košice. Data on mothers and new-born infants have been obtained from the birth book and from the reports on mothers at childbirth. For low birth weight we considered the weight of a new-born weighing less than 2,500 grams and as for premature birth we referred to childbirth before pregnancy week 37. The file was split by ethnicity and statistically processed in IBM SPSS Statistics 21.0. RESULTS: Our results confirmed a lower birth weight among Roma children (-365.4 grams, p < 0.001). The shorter gestation age and higher risk of premature birth were not statistically significant regarding Roma children. Based on the characteristics of Roma mothers, they are at higher risk of giving birth as minor (OR = 23.64; 95% CI = 15.29-36.54; p < 0.001), as single mothers (OR = 7.13; 95% CI = 5.80-8.76; p < 0.001), with basic education or lack of education (OR = 141.31; 95% CI = 100.47-198.76; p < 0.001). They also have a higher risk of smoking during pregnancy (OR = 23.84; 95% CI = 18.06-31.49; p < 0.001); drinking alcohol (OR = 11.71; 95% CI = 3.36-40.90; p < 0.001) and taking drugs (OR = 8.70; 95% CI = 1.81-42.02; p < 0.001). Roma women attended gynaecologists more rarely. CONCLUSION: It is therefore important to support the work of community health workers and stimulate collaboration between community health professionals, paediatricians and gynaecologists to overcome institutional barriers in maternity and child care for mothers living in Roma settlement.
Keywords: Premature Birth; dospělí; předčasný porod; Female; novorozenec; Birth Weight; Adult; ženské pohlaví; Slovakia; lidé; Infant, Newborn; porodní hmotnost; Infant, Low Birth Weight; Pregnancy Outcome; těhotenství; novorozenec s nízkou porodní hmotností; Risk Factors; retrospektivní studie; matky; Romové; Mothers; výsledek těhotenství; rizikové faktory; Roma; Slovenská republika; Pregnancy; Retrospective Studies; Humans